TINJAUAN YURIDIS PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL DALAM KERANGKA WTO DAN HUKUM NASIONAL INDONESIA - Irwan Soeharlim; Annie Myranika; Muhammad Ruhunussa; Anharyanto (CV. Lafadz Jaya, 2026)
International trade dispute settlement is an important instrument in maintaining the stability of the global trading system. The World Trade Organization (WTO) through the Understanding on Rules and Procedures Governing the Settlement of Disputes (DSU) provides a binding adjudicative mechanism for member states. This study aims to analyze the WTO dispute settlement mechanism, the implementation of WTO provisions in Indonesian national law, and the harmonization between international trade law and Indonesia’s national interests. This research uses a normative juridical method with statutory, conceptual, and case approaches. The results indicate that the WTO dispute settlement mechanism consists of consultation, panel proceedings, appeals, and implementation of decisions. Indonesia has adopted WTO principles into national regulations, particularly through Law Number 7 of 2014 concerning Trade and Law Number 24 of 2000 concerning International Treaties. However, harmonization between national law and WTO provisions still faces challenges, especially regarding the protection of national interests, downstream natural resource policies, and the WTO Appellate Body crisis. The DS592 nickel export dispute and DS480 biodiesel dispute demonstrate the dynamic relationship between international obligations and national economic sovereignty. Therefore, strengthening international trade law capacity and WTO reform are necessary to create a fairer and more balanced international trading system.